EFFECT OF SOME AGRICULTURAL TREATMENTS ON GROWTH AND YIELD OF LETTUCE Lactuca sativa L. - Mohammad Talal A. El-Habar; Mohammad Radhi S. Al-Saaberi (Mesopotamia Journal of Agriculture)
This study was conducted in vegetable farm in the college of Agriculture and Forestry, Mosul University during 2003-2004 growing season to investigate the effects of two sowing dates: the Sept.20th and Oct. 20th, two planting methods of seedling: plots and furrows and with the application of nitrogen fertilizer (Urea 46% N) at rates 0 and 60 Kg/Donnum applied at two doses with three methods of splitting: 1- Half of the total amount was added after two weeks from transplanting and the other half was added at 21 days prior to harvest (30 + 30Kg Urea /Donnum). 2- One third of the total amount added after two weeks from transplanting and the other two thirds was added at 21 days prior to harvest (20 + 40Kg Urea/Donnum). 3- Two thirds of the total amount added two weeks from transplanting and the other one third added at 21 days prior to the harvest (40 + 20Kg Urea/Donnum) on growth, yield and quality of lettuce cv. Paris Island. The experiment consisted of 16 treatments conducted in the field in a factorial experiment within split plot using the Randomized Complete Block Design with three replicates. Results indicated that vegetative growth i.e. leaf number/plant, leaf area/plant, head circumferences and mean weight of marketable head were increased significantly by second sowing date (Nov. 20th), plot planting method as well as by applying nitrogen fertilizer, while the methods of splitting of nitrogen fertilizer had no significant effect on most above mention characters. A similar favorable effect of second sowing date (No.20th), plot planting method and applying nitrogen fertilizer on yield characters was obtained at harvest, However, it has increased significantly folded head percentage, total and marketable yield, whereas the percentage of bolting plants only decreased significantly by second sowing date. The interaction among sowing date, plating methods, nitrogen application gave positive and significant increase in the total and marketable yield.